1989
DOI: 10.1002/anie.198913771
|View full text |Cite
|
Sign up to set email alerts
|

[Ir2(μ‐CH2)(CO)4 Me2PCH2P(Me2)2][CF3SO3]2, an Unprecedented Electrophilic Methylene Complex; H Addition to Prepare a Bridging Methyl Complex

Abstract: The first stable CH,-bridged transition metal complex was prepared by Herrmann et al. in 1975.") Since then, numerous pal kylidene complexes have been reported."] "Herrmann (1.6 M, 0.125 mol) was added at room temperature to a THF suspension (300 mL) of 1 a (20.0 g, 0.031 mol). An orange solution, containing some insoluble white solid formed, and then CIPPh, (22.8 mL. 0.125 mol) was added, keeping thc suspension at O.'C. The resulting light-brown solution was heated at 60 C for 2 h. The solvent was evaporated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

1993
1993
2005
2005

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 17 publications
(4 reference statements)
1
14
0
Order By: Relevance
“…Table contains a comparison of the pertinent geometric features of these three isomers [ IIIt , IIIb ( agostic ), and IIIb ( symmetric )]. In general, the parameters for IIIb ( symmetric ) agree reasonably well with those of the X-ray determination of the dmpm analogue, and in particular the calculated Ir−Ir bond length is comparable with that in the X-ray structure.…”
Section: Theoretical Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…Table contains a comparison of the pertinent geometric features of these three isomers [ IIIt , IIIb ( agostic ), and IIIb ( symmetric )]. In general, the parameters for IIIb ( symmetric ) agree reasonably well with those of the X-ray determination of the dmpm analogue, and in particular the calculated Ir−Ir bond length is comparable with that in the X-ray structure.…”
Section: Theoretical Resultssupporting
confidence: 75%
“…Compound 2 bears an interesting relationship to two previously reported dicarbonyl methyl compounds. In [Rh 2 (CH 3 )(CO)(μ-CO)(dppm) 2 ][CF 3 SO 3 ] 34 the methyl group is terminally bound to one rhodium center, whereas in [Ir 2 (CO) 2 (μ-CH 3 )(dmpm) 2 ][CF 3 SO 3 ] (dmpm = Me 2 PCH 2 PMe 2 ) the methyl group bridges the metals in a symmetrical fashion. The existence of these dicarbonyl, methyl complexes suggested that CO removal from 2 may reverse the C−H bond cleavage step, regenerating a related methyl product.…”
Section: Results and Characterization Of Compoundsmentioning
confidence: 99%
“…The exact analogue of these homobimetallic, dicarbonyl complexes can be generated through CO loss from 1 by refluxing in CH 2 Cl 2 to give [RhIr(CH 3 )(CO) 2 (dppm) 2 ][CF 3 SO 3 ] ( 2 ). Based on previous work, two structures seemed possible for 2 in the solid state, having the methyl group either terminally bound to one metal, as in the solid-state structures of [M 2 (CH 3 )(CO)(μ-CO)(dppm) 2 ][CF 3 SO 3 ] (M = Rh, Ir 1 ), or bridging the metals as in the dmpm analogue [Ir 2 (CO) 2 (μ-CH 3 )(dmpm) 2 ][CF 3 SO 3 ] (dmpm = Me 2 PCH 2 PMe 2 ) . The IR spectrum of 2 in the solid indicates that one carbonyl is terminal (1997 cm -1 ) and one is bridging (1858 cm -1 ).…”
Section: Results and Compound Characterizationmentioning
confidence: 99%
“…For dppm-bridged systems, the overwhelmingly favored conformation is the boat ( B ). The existence of the boatlike conformation for the dmpm A-frame [Ir 2 (μ 2 -CH 3 )(CO) 2 (dmpm) 2 ][CF 3 SO 3 ] and the chairlike conformation of the dppm A-frame Pd 2 (μ-CO)(OC(O)CF 3 ) 2 (dppm) 2 makes it difficult to unconditionally ascribe these conformational variations to electronic or steric effects from the diphosphine ligand substituents. However, given the rarity of chairlike conformations in the many dppm-bridged A-frame structures known, it can be concluded that steric demands of phenyl substituents on dppm ligands disfavor the chairlike conformation of the M 2 P 4 C 2 ring in contrast to what is observed for the title complex.…”
Section: Resultsmentioning
confidence: 99%